The effect of HIV infection and exposure on cognitive development in the first two years of life in Malawi. (March 2020) - Struyf, Thomas; Dube, Queen; Cromwell, Elizabeth A.; Sheahan, Anna D.; Heyderman, Robert S.; Van Rie, Annelies
Abstract: Objectives: To assess longitudinal patterns and determinants of cognitive development in infants living with HIV, infants exposed to maternal HIV infection, and HIV-unexposed infants. Methods: Prospective, community-based cohort study of 555 Malawian infants aged 8 weeks to 24 months, using multivariable linear mixed-effects regression models with random intercepts to analyze repeated measures of cognitive function. Results: At 3 months of age, cognitive scores on the Bayley Scales of Infant Development (BSID 3rd edition) were lower in the 96 HIV-infected infants (mean = 14.1 (SD:4.8)) compared to the 289 HIV-exposed (mean = 16.5 (SD:3.7)) and the 170 unexposed infants (mean = 17.5 (SD:3.3)). Over the first two years of life, the small deficit in cognitive development of infants living with HIV who survived and remained in care did not increase (mean score 52.9 among HIV-infected vs 55.6 among HIV unexposed). In multivariable analysis, malnutrition and a more advanced clinical infant HIV stage had a negative impact on cognition at age 3, while financial security, care by the biological mother, and ART for mother and child were associated with better cognitive status at this young age. The positive influence of maternal ART reversed with age. Conclusions: Malawian infants exposed to HIV had a cognitive development that was similar to their unexposed peers in the first two years of life, while that of HIV infected infants lagged behind from the start. Early initiation of effective ART in all HIV infected mothers and infants, and prevention of infant malnutrition are important to safeguard cognitive development of children affected by HIV. Highlights: Infants living with HIV had a small cognitive deficit at age 3 months. This deficit did not increase, if they were effectively treated. Cognition of HIV-exposed uninfected children was similar to that of the unexposed. Early initiation of effective ART in both mothers and infants is essential. Malnutrition has a negative impact on early cognition in HIV infected children.